Assessing the integrity of auditory processing and sensory memory in adults with cystinosis (CTNS gene mutations) - Ana A. Francisco; Alaina S. Berruti; Frederick J. Kaskel; John J. Foxe; Sophie Molholm (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Cystinosis, a rare lysosomal storage disease, is characterized by cystine crystallization and accumulation within tissues and organs, including the kidneys and brain. Its impact on neural function appears mild relative to its effects on other organs, but therapeutic advances have led to substantially increased life expectancy, necessitating deeper understanding of its impact on neurocognitive function in adulthood. We previously demonstrated intact auditory sensory processing, accompanied by mild sensory memory difficulties, in children and adolescents with cystinosis. Methods We investigated whether further progressive decrements in these processes would be observed in adults with cystinosis, comparing high-density auditory-evoked potential (AEP) recordings from adults with cystinosis (N = 15; ages: 19–38 years) to those of age-matched controls (N = 17). We employed a duration oddball paradigm with different stimulation rates, in which participants passively listened to regularly occurring standard tones interspersed with infrequently occurring deviant tones. Analyses focused on AEP components reflecting auditory sensory-perceptual processing (N1 and P2), sensory memory (mismatch negativity, MMN), and attentional orienting (P3a). Results Overall, adults with cystinosis produced highly similar sensory-perceptual AEP responses to those observed in controls suggesting intact early auditory cortical processing. However, significantly increased P2 and P3a amplitudes and reduced MMN at slower stimulation rates were observed, suggesting mild-to-moderate changes in auditory sensory memory and attentional processing. While cognitive testing revealed lower scores on verbal IQ and perceptual reasoning in cystinosis, these did not correlate with the AEP measures. Conclusions These neurophysiological data point to the emergence of subtle auditory processing deficits in early adulthood in cystinosis, warranting further investigation of memory and attentional processes in this population, and of their consequences for perceptual and cognitive function.